Ertugliflozin in the treatment of type 2 diabetes mellitus - Joel C Marrs; Sarah L Anderson (BioExcel Publishing Ltd, 2020)
More than 422 million people worldwide have diabetes, with 90-95% having type 2 diabetes (T2D). Glycemic control of T2D has demonstrated reductions in microvascular complications but recent data have demonstrated improvements in macrovascular outcomes with sodium-glucose cotransporter 2 (SGLT2) inhibitors. Ertugliflozin is the most recent SGLT2 inhibitor approved in the USA and Europe for the treatment of T2D. This narrative review aims to present and discuss the efficacy, safety, cardiovascular (CV), and renal outcomes related to the use of ertugliflozin in T2D. Ertugliflozin has been evaluated in eight clinical trials (n=5248) with a focus on glycemic control. These trials have demonstrated improvement in glycosylated hemoglobin (0.6-1%), fasting plasma glucose (30-50 mg/dL), 2-hour postprandial glucose (60-70 mg/dL), decreased body weight (2-3 kg), and lowering of blood pressure (3-5 mmHg) in patients with T2D when ertugliflozin is used as monotherapy or in addition to metformin, sitagliptin, insulin, and/or sulfonylureas. The findings from the VERTIS-CV trial (n=8246) were recently published and demonstrated that ertugliflozin use in patients with T2D and atherosclerotic CV disease is safe but did not demonstrate superiority in the lowering of major CV events compared to placebo. Other SGLT2 inhibitors, such as empagliflozin and canagliflozin, have demonstrated this benefit. The VERTIS-CV trial demonstrated that the use of ertugliflozin led to a decrease in the number of hospitalizations for heart failure and this lends further support that this benefit is a class effect of SGLT2 inhibitors.